Risk and social vulnerability: how engineering can engage more effectively with climate change - El-Zein, Abbas H. (Frontiers in Environmental Science, 2014)
Engineering practice, education and research are bound to be important elements in society’s response to climate change. While a number of other disciplines such as economics, agriculture, urban planning and geoscience, are critical to the development of mitigation policies, the designs and processes engineers create in the transport, mining, energy, building and waste management sectors will be key in determining atmospheric concentrations of greenhouse gases over the coming decades. Similarly, the way landscapes, buildings, neighbourhoods and cities are built or rebuilt, will undoubtedly be a major part of adaptation to higher temperatures, rising sea levels and more extreme weather events. The paper discusses some of the barriers that prevent engineering education and practice from fully and productively engaging with the challenges raised by climate change. The paper recommends an expansion of the solution universe to which engineering students and graduates are exposed, a better understanding by engineering students of the politics of technology and possible biases of engineers, and more engagement on the part of engineers with the social and ecological embeddedness of technology.